REDOX STRATIFICATION AND HEAVY METAL PARTITIONING IN AVICENNIA-DOMINATED MANGROVE SEDIMENTS: A GEOCHEMICAL MODEL - Clark M.W.; McConchie D.; Lewis D.W.; Saenger P. (My University, 1998)
Mangrove forest sediments can provide a sink for trace metals because the mangroves create a baffle that promotes the accumulation of fine-grained organic matter-rich sediment, which is usually sulphidic due to the presence of sulphate-reducing bacteria. Direct adsorption, complexing with organic matter, and the formation of insoluble sulphides all contribute to the trapping of metals. The concentration and chemical speciation of the metals are influenced by the distribution of geochemically distinct horizons within the sediment. In horizons with a pH>7 and an Eh<-150 mV (reduction horizons), metals are largely present as sulphide-bound species, whereas in horizons with a pH<7 and an eh>+100 mV (oxidation horizons), most metals are present as exchangeable or oxide-bound species. In most cores, two oxidation and two reduction horizons can be recognised, but dark mottles of low Eh (<-150 mV) sediment can be found in the oxidation horizons, and orange-brown halos of high Eh (>+100 mV) sediment can be found around mangrove roots and burrows in the reduction horizons. The depth to each horizon, differs between cores and can change in response to seasonal shifts in the position of the water table. A model is presented that accounts for the development of the oxidation and reduction horizons within the Avicennia-dominated mangrove forest sediment and describes the major controls on metal cycling within the sediment.
Keywords: HEAVY METAL PARTITIONING; REDOX STRATIFICATION; MANGROVE SEDIMENTS; AVICENNIA